Characteristics of activated carbon derived from Camellia oleifera cake for nickel ions adsorption. (April 2023) - Quan, Cui; Wang, Weiding; Su, Jinzhan; Gao, Ningbo; Wu, Chunfei; Xu, Guoren
Abstract: This study used Camellia oleifera cake to prepare activated carbon (AC) for nickel removal from aqueous solutions. After carbonization at 700 °C for 2h, activation was subsequently carried out with four different activators (Na2 CO3, KOH, NaOH, H3 PO4 ). The results showed that the four ACs had well-developed microporous structures. The AC with NaOH activation had the highest specific surface area of 512.18 m 2 g −1, and the largest pore volume of 0.356 cm 3 g −1 . The adsorption of Ni(II) on the ACs showed that the removal ratio of Ni 2+ reached 95.7% at 25 °C on AC with Na2 CO3 activation when the input amount was 5 g L −1, while AC with NaOH as activator had the highest Ni 2+ removal ratio of 86.75% when the input amount was 1g L −1 at 25 °C. In addition, the adsorption capacity of AC was increased when the temperature rose between 25 and 60 °C. Compared to pseudo-first-order (PFO) model, the adsorption of Ni 2+ on ACs is better suited by pseudo-second-order (PSO) model, and the ion precipitation in chemical adsorption is proved as adsorption mechanism. Graphical abstract: Image 1 Highlights: Small molecule gases produced in activation process are favorable for pore forming. The activated carbon prepared by NaOH and KOH has better physical properties. Ion precipitation is the form of nickel ion adsorption. The adsorption mechanism of nickel ion is monolayer chemisorption.